Spinel‐type mixed oxides for stable and selective partial oxidation of benzyl alcohol - Gurrala, Lakshmiprasad; Nagpure, Atul S.; Gurav, Hanmant R.; Chilukur, Satyanarayana (ChemistrySelect, 2018)
Benzaldehyde is an important chemical intermediate, which need to be prepared through an eco‐friendly process. Manganese oxides are active as catalysts for its preparation through partial oxidation of benzyl alcohol. In this study, Cu, Co and Mn containing spinel based mixed oxides (CuxMn3−xO4) were prepared and tested for partial oxidation of benzyl alcohol to get benzaldehyde with high selectivity. The catalytic activity strongly depended on chemical composition, acid‐base properties and oxygen uptake. The influence of chemical composition, reaction temperature, oxygen partial pressure and the weight hourly space velocity (WHSV) were investigated to optimize benzaldehyde yield and to stabilize the catalyst activity. A high benzaldehyde selectivity of 98%, accompanied with benzyl alcohol conversion of 84.5% was obtained over Cu0.25Mn2.75O4 catalyst at 300 °C. It was evident from temperature programmed desorption (TPD) of CO2 that this catalyst was found to have optimum basicity and high oxygen uptake, thus imparting high activity and stability. Activity and catalyst life could be attributed to appropriate acid‐base properties. Supporting Information